Analisis Kemampuan Berpikir Kreatif Siswa dengan Pendekatan Matematika Realistik di Kelas VA MIN lll Kota Mataram - Rizka Maulida Rohimana; Syuhada’ Nuzula; Djuita Hidayati (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research was conducted to find out the extent of students' thinking skills using a realistic mathematical approach or the realistic mathematic education (RME) approach. This approach uses a qualitative method with a descriptive qualitative approach. The tenic used is observation and wawwancara. This research was conducted by us Mataram State Islamic University students. This study is located in MIN LLL Mataram City precisely in class V teachers. The researcher also analyzes with qualitative data analysis, based on the results obtained from observations and interviews, it shows that students' creative thinking skills use realistic mathematical approaches are still less, because teachers need a long time To be able to make students understand related to learning mathematics using PMR, and students assume that learning mathematics is very difficult.